2012
DOI: 10.1179/1362171812y.0000000049
|View full text |Cite
|
Sign up to set email alerts
|

Effect of materials position on friction stir lap welding of Al to Cu

Abstract: Friction stir welding has been successfully used to weld the dissimilar metals. A few investigations have been carried out on the friction stir lap welding of Al to Cu, but the basic issue of how the position of the metals would affect the joint strength is still not resolved. In the present study, the 7070 Al and the commercially pure copper are lap joined using friction stir lap welding technology. Two test cases are considered. The distinction refers to the position of Al with respect to Cu. Microstructural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 23 publications
0
51
0
Order By: Relevance
“…While the intermixing is minimized at 1.8 mm, the extrusion of single copper fragments can be observed at 2 mm pin length. These fragments show a typical layer structure, which has repeatedly been observed in Al/Cu joints and identified as mostly intermetallic compounds [28][29][30]. It can be assumed that the pronounced IMC formation occurs when fragments are detached from the copper base material and are transported around the pin, presumably for numerous revolutions.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…While the intermixing is minimized at 1.8 mm, the extrusion of single copper fragments can be observed at 2 mm pin length. These fragments show a typical layer structure, which has repeatedly been observed in Al/Cu joints and identified as mostly intermetallic compounds [28][29][30]. It can be assumed that the pronounced IMC formation occurs when fragments are detached from the copper base material and are transported around the pin, presumably for numerous revolutions.…”
Section: Resultsmentioning
confidence: 67%
“…Galvao et al [28] observed increased intermixing, IMC formation and void formation for lap joints of pure copper and EN AW5083/AW6082, respectively, when copper is directly processed by the tool shoulder. Investigations of Akbari et al [29] showed an up to 26% increased peak temperature in this configuration. In terms of heat and wear minimization, most investigations are therefore carried out with aluminium as the top sheet.…”
Section: Introductionmentioning
confidence: 67%
“…FSP has been invented based on friction stir welding (FSW) for the microstructure modification of materials [7,8], which results in improving their mechanical and wear resistance. FSW as a welding technique has been used to weld different Al [8,[13][14][15][16], Mg [7,17,18], and Cu [13,19] alloys, some of which are classified as practically unweldable alloys in use of conventional welding methods. Different surface composites have been produced with different types of reinforcing particles like SiC [7,20], TiC [21], Al 2 O 3 [22], CNT [23][24][25], TiO 2 [26], and B 4 C [27].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the welds produced under very high heat input conditions (high rotation speed and low traverse speed) presented formation of brittle intermetallic layers, in which strong micro-cracking takes place, the welds carried out under low heat input conditions (low rotation speedand high traverse speed) displayed incompletely welded interfaces. Akbari et al [3] analyzed the effect of base materials positioning on friction stir lap welding of 2 mm-thick plates of AA 7070 aluminium alloy to commercially pure copper. Welds produced with the aluminium alloy located on the top of joint and the copper at the bottom, as well as welds carried out with the reverse base materials positioning, were studied by the authors.…”
Section: Welding Of Aluminium Alloys a Aluminium To Cumentioning
confidence: 99%